Implementasi Model Dick and Carey dalam Pengembangan Pembelajaran Pendidikan Agama Islam di Sekolah Dasar - Mulyawan Safwandy Nugraha; Nurul Husna; Tarsono Tarsono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2024)
The ability to design lesson planning is an ability that must be possessed by educators. This model is a design model that offers a continuous process and corresponds to this competence in PAI learning. This research implements a field research model with a descriptive qualitative approach. This research was conducted at SDN 258 Voluntary Bandung City which aimed to see the results of the implementation of the dick and carey model in the development of PAI learning in elementary schools. The research data was obtained from interviews with Islamic Religious Education teachers and students. Observations were made on the implementation of the dick and carey model in the PAI learning process. Documentation in the form of a review of teaching modules. Analysis techniques include data reduction, data verification and conclusions. The results of the study stated the steps applied in the implementation at SDN 258 Voluntary including first, identifying learning objectives Second, conducting teaching analysis. Third, identify data on students' behavior and their personalities. Fourth, describe the purpose of performance. Fifth, formulate benchmark reference test items. Sixth, use relevant learning strategies. Seventh, sort and develop teaching materials. Eighth, designing and developing formative evaluations in the form of teaching and learning activities. Ninth, revise the learning program.